2021
DOI: 10.1016/j.jhepr.2021.100332
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte dysfunction in decompensated cirrhosis is mediated by the prostaglandin E2-EP4 pathway

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Unknown concentrations were determined via interpolation to a reference curve generated from a series of known PGE 2 concentration assays. Our previous study has shown that although EIA measurements of PGE 2 were as much as ×20 higher than liquid chromatography–tandem mass spectrometry, EIA reproducibly produced qualitative differences between sample groups consistent with data from liquid chromatography–tandem mass spectrometry analysis ( 16 ).…”
Section: Methodssupporting
confidence: 77%
“…Unknown concentrations were determined via interpolation to a reference curve generated from a series of known PGE 2 concentration assays. Our previous study has shown that although EIA measurements of PGE 2 were as much as ×20 higher than liquid chromatography–tandem mass spectrometry, EIA reproducibly produced qualitative differences between sample groups consistent with data from liquid chromatography–tandem mass spectrometry analysis ( 16 ).…”
Section: Methodssupporting
confidence: 77%
“…Albumin was also recently incorporated into the MELD 3.0 score [ 21 ] and our results suggest these changes may improve MELD-based prognosis of HCC progression compared to the MELD-Na. Beyond direct effects of albumin on HCC biology, the role of prostaglandin E2-mediated depletion of albumin stores in advancing CAID and its role in systemic immune suppression are becoming clearer [ 11 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors secondly explored how the PGE2 pathway modulate monocyte dysfunction in patients with AD, who might benefit the most from intervention to prevent ACLF. They reported that PGE2 is produced by both hepatocytes and circulating monocytes mainly via the COX-/microsomal PGES-1 and COX-2 pathways respectively ( 114 ). In this study, through a specific antagonist approach, PGE2 was shown to mediate monocyte dysfunction mainly via its EP4 receptor (instead of EP2) ( 114 ).…”
Section: Eicosanoidsmentioning
confidence: 99%
“…They reported that PGE2 is produced by both hepatocytes and circulating monocytes mainly via the COX-/microsomal PGES-1 and COX-2 pathways respectively ( 114 ). In this study, through a specific antagonist approach, PGE2 was shown to mediate monocyte dysfunction mainly via its EP4 receptor (instead of EP2) ( 114 ). In HBV-related ACLF, an increase in circulating PGE2 was also observed.…”
Section: Eicosanoidsmentioning
confidence: 99%